KONSEP MAX WEBER TENTANG KEPEMIMPINAN KHARISMATIK - Muchtarom (UNIBA Surakarta), Zaini (Manajemen Bisnis Syariah, 2011)
Leaderships crisis experienced by Indonesia wakes people to seek figurepof leader who can develop trust in which has lost from people´s heart. DoesIndonesia need a charismatic leader ? There many questions to be answeredregarding the charismatic leaderships.Max Weber views ang thought is offered toanswer the questions.Max Weber wasborn in Erfurt Germany in April 1864 is an author of a wellknown book “ The Protestant Ethic and the Spirit of Capitalism” which motivatesand inspires the growth of capitalism.Weber always used the term charisma in thesense of an extraordinary quality possessed by persons or objects that is thought togive these persons or objects a unique, magical power.Weber´s concept regarding charismatic leaderships based on theologywhich is developend from social science. Prophet is a model of perfect charismaticleader, therefore it is regarded as leader and savior in crisis.Keywords : concept, leader, charisma, prophet.